Efeitos da quarentena durante a pandemia de COVID-19 no padrão do sono em uma população com narcolepsia - Aguilar, Ana Carolina Rodrigues [UNIFESP] (2021)
Study Objectives: To the best of our knowledge, there has not as yet been any study on the effects of the COVID-19 pandemic on patients with narcolepsy; in particular in relation to its impact on sleep schedules, symptoms, the need for medication, work, income, and quality of life. This study therefore aimed to explore these factors and their possible influence on sleep, circadian timing and narcolepsy symptoms during the pandemic. Methods: Patients with narcolepsy who had been in quarantine for at least three months completed an online questionnaire. Questions targeted the conditions of the quarantine, sleep-related behaviors, and factors known to affect sleep and circadian rhythms (work status, income, appetite, narcolepsy symptoms, and medication), as well as the quality of life during the quarantine period. Results: The routines of the participants had been altered by quarantine, with changes in their place of work, and an increase in narcolepsy symptoms such as cataplexy, sleep paralysis, hallucinations, nocturnal awakenings, and sleepiness. Sleep and wake times changed, resulting in altered sleep patterns in the majority of the sample. No association between changes in the place of work and narcolepsy symptoms was found. Regarding medication, the participants used fewer antidepressant pills but took more stimulants. Appetite was increased and self-reported quality of life decreased during the period. Conclusions: During the quarantine the patients with narcolepsy reported worsening of narcolepsy symptoms and increased use of stimulants, furthermore was observed changes in their bedtime and waking-up schedules, suggesting a tendency to circadian misalignment. In Brazil, the effects of the COVID-19 outbreak have gone beyond the direct action of the virus, because of the collateral damage it has caused in respect of unemployment and financial hardship. These impacts have been amplified in Brazil because of the level of social inequality found in the country, and they have particularly affected vulnerable patients with rare diseases, such as the narcolepsy population.